Vegetable farm structure evolution by standard output - Cornelia Alboiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The relationship between farm size and land productivity has been widely debated in literature for decades and several reasons and explanations for the inverse relationship between farm size and land productivity .The paper presents the evolution of areas under vegetables by size classes and regions according to standard output. The main methodological tool used is statistical analysis and comparisons among regions. The results reveal the perpetuation of the very small-sized farms, with low economic power, across regions, with a slightly decreasing trend of their number, under the background of increasing the cultivated areas under greenhouses and plastic tunnels.
Keywords: Q11; Q13; 330; farm productivity; vegetable farm structure